IMPACTS OF USING POROUS CORNER PARTITIONS AND BLADE SHAPED NANOPARTICLES IN BASE FLUID ON THE PERFORMANCE IMPROVEMENT OF THERMOELECTRIC GENERATOR MOUNTED VENTED CAVITIES AND INTERFACE TEMPERATURE ESTIMATION WITH PROPER ORTHOGONAL DECOMPOSITION - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Begell House Inc, 2024)
Numerous technical applications, such as solar power, refrigeration, waste heat recovery, thermal management, and many more, employ thermoelectric devices because of the numerous advantages they offer. Techniques are required to improve their effectiveness in usage. In this study, a unique technique for improving the performance of a thermoelectric generator (TEG) positioned between vented cavities is proposed. The method combines the effects of blade-shaped nanoparticles in the base fluid and corner porous partitions. A numerical study using the finite element method is conducted for different values of Darcy number of upper and lower cavity (10(-6) <= Da(1) <= 10(-2), 10(-6) <= Da(2) <= 10(-2)), opening ratio (SR between 0.5 and 2.5), and nanoparticle loading amount (SVF between 0 and 0.03). By adjusting the permeability of the partitions and opening ratio of the cavities, significant changes in the flow field can be obtained. TEG power increases with greater opening ratios and lower partition permeabilities. By changing the permeability, the TEG power can increase by up to 27.5 percent, while increasing the opening ratio from SR = 0.5 to SR = 1 can increase the TEG power by up to 140 percent. Using blade-shaped nanoparticles results in additional improvements, with values of 32.7% at SR = 0.5 and 20.26% at SR = 2.5. Using 180 parametric computational fluid dynamics cases, a POD-based low-cost reconstruction model is created for the interface temperatures at the hot and cold sides using five-POD modes. The method may be used for other complicated geometries where 3-D computations are costly and allows for the rapid computation of coupled TEG-vented cavity systems with corner partitions.
Keywords: porous partition; vented cavity; thermoelectricity; FEM; blade-shaped nanoparticle; POD